Settler colonialism and (re)conciliation: frontier violence, affective performances, and imaginative refoundings - Edmonds, Penelope (Cambridge imperial and post-colonial studies series, 2016)
"This book explores reconciliation's performative life and its discontents in settler societies. It explores the affective refoundings of the settler state and the radical reimagining of its alternatives by Indigenous peoples and allied others, and, in particular the way the past is creatively mobilized, reworked and enlisted in the name of social transformation within a new global paradigm of reconciliation and the 'age of apology' ... taking selected case studies across the postcolonial settler societies of the United States of America, Australia, and Aotearoa New Zealand"--Introduction